Insights into the concept of fish welfare - Volpato, Gilson Luiz; Goncalves-de-Freitas, Eliane; Fernandes-de-Castilho, Marisa (Inter-research, 2007)
Fish welfare issues are predicated on understanding whether fish are sentient beings. Therefore, we analyzed the logic of the methodologies used for studying this attribute. We conclude that empirical science is unable to prove or to disprove that fish are sentient beings. Thus, we propose a combined ethical-scientific approach for considering fish as sentient beings. The most difficult ongoing question is to determine which conditions fish prefer. Approaches to assess fish preferences should be rigorously and cautiously employed. In light of these considerations, attempts to establish physiological standards for fish welfare are discouraged, and a preference-based definition of fish welfare is proposed.
Keywords: welfare; pain; stress; aquaculture; consciousness; sentience; preference fish